Peran Kepala Sekolah Didalam Lembaga Pendidikan Islam - Guntur Guntur; Idi Warsah; Dewi Purnamasari (LPPM IAIN Sorong, 2023)
: The role of the principal is to direct the implementation of teaching and learning in schools. As an educational leader, the principal must know and understand his duties and responsibilities and apply them correctly. The purpose of this study is because the authors are interested in the role of school principals in the management of Islamic education institutions: an analysis of leadership theory. Research by library research. relating to research. This research was carried out in a series of activities to collect, process and analyze data taken from written literature. Thus this research is called library research. The results of the first study are the principal as an educator, second, the principal as a manager, third, the principal as an administrator, fourth, the principal as a supervisor, fifth, the principal as a leader, sixth, the principal as a creator of the work climate, Seventh, the principal as an entrepreneur and the principal has the task of setting teacher standards in schools.